2023
DOI: 10.31219/osf.io/z3sj6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

New Physics is often not so new

Abstract: Based on both the strength of the Standard Model (SM), often lamented by some looking to evolve it, and the results obtained in the multi-fold theory that can qualitatively answer many open issues with SM and the Standard Cosmological Model (ΛCDM), we argue that typically, the recent widely published hints of New Physics aren’t. In fact they usually are not confirmed by later experimentations, or other theories, or the SMG, the standard model with gravity effects non-negligible at its scales, which we do not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In [27-29], we showed that space time matter induction and scattering can give the (fermions and scalar) particles of the SM. In [1,10,29,32,64,92,122,123,148] and references therein, we see that algebra doubling on non-commutative geometry in 4D also predicts the SM particles including neutrino mixing. The embedding space is non-commutative at small scales, per the properties of the multi-folds [1,32].…”
Section: Physics In the Embedding Spacementioning
confidence: 98%
See 2 more Smart Citations
“…In [27-29], we showed that space time matter induction and scattering can give the (fermions and scalar) particles of the SM. In [1,10,29,32,64,92,122,123,148] and references therein, we see that algebra doubling on non-commutative geometry in 4D also predicts the SM particles including neutrino mixing. The embedding space is non-commutative at small scales, per the properties of the multi-folds [1,32].…”
Section: Physics In the Embedding Spacementioning
confidence: 98%
“…Section 3 justifies starting from Spin(7,7) for the embedding space (spin(7) squared, or doubled) to be associated to spinning solutions in 7D, where we distinguished with a label those that result into left-handed vs right-handed solitons in 4D, i.e. spinning one way or another; hence squaring the symmetry, which, we have and will see, is also key as a consideration as in [1,10,29,32,64,92,122,123,148] and references therein.…”
Section: Physical or Microscopic Justifications Of The Multi-fold And...mentioning
confidence: 99%
See 1 more Smart Citation